Insecticidal and biochemical effects of Dillenia indica L. leaves against three major stored grain insect pests - Singh, Kabrambam D.; Koijam, Arunkumar S.; Bharali, Rupjyoti; Rajashekar, Yallappa (Frontiers in Plant Science, 2023)
The Last four decades have witnessed the banning of several synthetic insecticides mainly due to the development of resistance to the target pests and due to hazardous effects on humans and the environment. Hence, the development of a potent insecticide with biodegradable and eco-friendly nature is the need of the hour. In the present study, the fumigant property, and biochemical effects of Dillenia indica L. (Dilleniaceae) were studied against three coleopterans stored-products insects. The bioactive enriched fraction (sub-fraction-III) was isolated from ethyl acetate extracts of D. indica leaves and found toxic to rice weevil, Sitophilus oryzae (L.) (Coleoptera); lesser grain borer Rhyzopertha dominica (L.) (Coleoptera) and red flour beetle, Tribolium castaneum (Herbst.) (Coleoptera) with the LC50 values of 101.887, 189.908 and 115.1 µg/L respectively after 24 h exposure. The enriched fraction was found to inhibit the function of acetylcholinesterase (AChE) enzyme when tested against S. oryzae, T. castaneum, and R. dominica with LC50 value of 88.57 µg/ml, 97.07 µg/ml, and 66.31 µg/ml respectively, in in-vitro condition. It was also found that the enriched fraction caused a significant oxidative imbalance in the antioxidative enzyme system such as superoxide dismutase, catalase, DPPH (2,2-diphenyl-1-picrylhydrazyl), and glutathione-S-transferase (GST). GCMS analysis of the enriched fraction indicates three major compounds namely, 6-Hydroxy-4,4,7a-trimethyl-5,6,7,7a-tetrahydrobenzofuran-2(4H)-one, 1,2-Benzisothiazol-3(2H)-one, and Benzothiazole, 2-(2-hydroxyethylthio)-. Finally, we concluded that the enriched fraction of D. indica has insecticidal properties and the toxicity may be due to the inhibition of the AChE enzyme in association with oxidative imbalance created on the insect's antioxidant enzyme systems.